An Approach to Emergency Situation Forecasting in the Field of Road Maintenance Based on Big data Analysis - M. Mikliaev, E.; I. Antonova, I.; V. Nikonov, V.; G. Magomedov, S. (International Journal of Engineering and Technology, 2018)
The article considers the approach to forecasting emergency situations in the field of road maintenance by the example of bituminous concrete pavement, the wear of bituminous concrete pavement is calculated, dependences on temperature and humidity are determined, a mathematical model and algorithm are proposed, and an information system for forecasting emergency situations is developed.Â